Associations Between Acculturation, Depressive Symptoms, and Life Satisfaction Among Migrants of Turkish Origin in Germany: Gender- and Generation-Related Aspects - Morawa, Eva; Brand, Tilman; Dragano, Nico; Jöckel, Karl-Heinz; Moebus, Susanne; Erim, Yesim (Frontiers in Psychiatry, 2020)
Abstract Objective: The aim of the present study was to investigate the degree of depressive symptoms and life satisfaction (LS) as well as the association between acculturation and depressive symptoms among a large sample of persons with Turkish migration background in Germany, taking into account gender- and migration-related differences. Methods: This study was part of a pretest for a large national epidemiological cohort study in Germany. Acculturation was measured using the Frankfurt Acculturation Scale (FRACC). Based on the median split of the two subscales, four acculturative strategies according to integration, assimilation, separation and marginalization (Berry) were determined. Depressive symptoms were assessed with the depression module (PHQ-9) from the Patient Health Questionnaire. LS was assessed with a single item on a scale from 1 = bad to 5 = excellent. Differences in levels of depressive symptoms and LS in relation to gender and generation of migration were tested with analysis of covariance, controlling for age. Gender-stratified multiple linear regression analyses were also conducted for depressive symptoms as criterion variable. Results: 328 Turkish migrants participated (61.3% women). The cut-off-value of ≥10 was achieved by 33.2% of the women and 26.4% of the men (p=0.209). In female migrants, the age-adjusted mean score for depressive symptoms was 7.81 (SD=6.42), in males 6.70 (SD=6.41) (p=0.137). No significant gender-specific difference was found concerning age-adjusted mean score for LS (p=0.547). In both sexes, the second generation demonstrated a significantly higher age-adjusted mean score for LS of small/medium effect size than the first generation. In women, separation as acculturation style (linear regression coefficient (B)=4.05, 95% CI=1.34, 6.75, p=0.004; reference: integration) and having no partnership (B=2.50, 95% CI=0.20, 4.81, p=0.034) were associated with higher severity of depressive symptoms; in men, separation as acculturation style (B=4.26, 95% CI=1.15, 7.37, p=0.008; reference: integration) and employment status (B=-3.47, 95% CI=-5.76, -1.18, p=0.003) were related to depression levels. Conclusions: Separation as acculturation strategy is associated with higher levels of depressive symptoms (for both genders). Gender-sensitive health promotion programs should target separated migrants to improve their integration into the German society.